2011
DOI: 10.1007/s00330-011-2225-0
|View full text |Cite
|
Sign up to set email alerts
|

Contrast induced nephropathy: updated ESUR Contrast Media Safety Committee guidelines

Abstract: Topics reviewed include the definition of CIN, the choice of contrast medium, the prophylactic measures used to reduce the incidence of CIN, and the management of patients receiving metformin. Key Points • Definition, risk factors and prevention of contrast medium induced nephropathy are reviewed. • CIN risk is lower with intravenous than intra-arterial iodinated contrast medium. • eGFR of 45 ml/min/1.73 m (2) is CIN risk threshold for intravenous contrast medium. • Hydration with either saline or sodium bicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
664
4
29

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 776 publications
(733 citation statements)
references
References 152 publications
10
664
4
29
Order By: Relevance
“…Current guidelines recommend monitoring SCr post CM exposure to detect CI‐AKI 5. Clinical studies also revealed that CyC is a reliable biomarker of CI‐AKI 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines recommend monitoring SCr post CM exposure to detect CI‐AKI 5. Clinical studies also revealed that CyC is a reliable biomarker of CI‐AKI 14.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is critical for patients because CI‐AKI causes time‐related injury to the kidney 4. CI‐AKI is now typically defined as an increase in serum creatinine (SCr), meeting one of several criteria, and occurring within 72 hours after intravascular administration of contrast medium (CM) 5. However, creatinine is an unreliable index of CI‐AKI because it is an indirect and insensitive indicator during acute changes in kidney function 4.…”
Section: Introductionmentioning
confidence: 99%
“…Although contrast‐induced acute kidney injury (CIAKI) is usually reversible, blood purification is required or irreversible kidney dysfunction may develop in some patients and renal survival is shortened 8. Injection of contrast medium promotes secretion of endothelin, a vasoconstrictor peptide produce by endothelial cells, by the renal parenchyma and the resulting vasoconstriction reduces renal tissue blood flow and oxygen supply 9.…”
Section: Areas Where Clinical Application Of Hydrogen Gas Is Expectedmentioning
confidence: 99%
“…Contrast agent should be used in compliance with the recommendations of the ESUR (European Society of Urogenital Radiology) [23]. The known contraindications for intravenous contrast agent application are for example contrast agent allergy, renal insufficiency, untreated hyperthyroidism, and plasmacytoma.…”
Section: Contrast-enhanced Ctmentioning
confidence: 99%